2011
DOI: 10.1177/0266242610390594
|View full text |Cite
|
Sign up to set email alerts
|

Integrating motivation, risk-taking and self-identity: A typology of ICT enterprise development narratives

Abstract: This article describes an original typology of enterprise development narratives that emerged from a study of the motivation, risk-taking and self-identity of nascent ICT (information and communications technology) entrepreneurs. The typology provides a multifaceted and integrated framework for appreciating an entrepreneur’s quest to align ‘who I am and what I do’ and achieve what we are calling the ‘self-enterprise fit’. As such, it promises to provide a valuable framework for (re)locating the ‘psychology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 83 publications
2
36
1
Order By: Relevance
“…Differences in risk perception may result, in turn, in some individuals (here, entrepreneurs) choosing riskier paths because they believe they can master them (Busenitz, 1999). Mills and Pawson's (2012) literature survey confirmed that risk-taking is a critical variable for understanding enterprising behaviour, and they IJGE 7,1 consider the variable to be a cornerstone of any decision to start a business. This is consistent with other previous research that has demonstrated a significant relationship between risk tolerance and entrepreneurial behaviour (Barbosa et al, 2007;Karakowsky and Elangovan, 2001;Keh et al, 2002;Sitkin and Pablo, 1992;Sitkin and Weingart, 1995).…”
Section: Theory and Hypotheses Risk Perceptions Entrepreneurship Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Differences in risk perception may result, in turn, in some individuals (here, entrepreneurs) choosing riskier paths because they believe they can master them (Busenitz, 1999). Mills and Pawson's (2012) literature survey confirmed that risk-taking is a critical variable for understanding enterprising behaviour, and they IJGE 7,1 consider the variable to be a cornerstone of any decision to start a business. This is consistent with other previous research that has demonstrated a significant relationship between risk tolerance and entrepreneurial behaviour (Barbosa et al, 2007;Karakowsky and Elangovan, 2001;Keh et al, 2002;Sitkin and Pablo, 1992;Sitkin and Weingart, 1995).…”
Section: Theory and Hypotheses Risk Perceptions Entrepreneurship Andmentioning
confidence: 98%
“…Fourth, risk behaviours are considered a cornerstone of entrepreneurship, and therefore, the research on the relationship between risk factors and entrepreneurial activities is extensive (Mills and Pawson, 2012). However, the need still exists for more research in the field (Barbosa et al, 2007;Brindley, 2005;Zhao et al, 2005).…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…Social identity theory is thus interested in the social identities gained from group memberships (Brown 2000;Mills and Pawson 2011), and the person defines himself or herself as a member of a group or social category. Again, individuals do not usually have a single social identity but more often have hybrid identities (Fauchart and Gruber 2011), whereby individuals occupy several social identities that can overlap, enrich one another and conflict (Chasserio, Pailot, and Poroli 2014;Hytti 2005;Essers andBenschop 2007, 2009;Down and Warren 2008).…”
Section: Entrepreneurial Identitymentioning
confidence: 99%
“…Hence, an entrepreneur with a particular frame of reference related to his/her identity will use the same frame of reference in the entrepreneurial decisionmaking process related to entrepreneurial behaviour. Hence, there needs to be a fit between the identity and the enterprising activity (Mills and Pawson 2011). Because entrepreneurship research often reports self realization or the ability to express oneself as an important motivation behind entrepreneurs starting new ventures and entering into entrepreneurship (Van Gelderen and Jansen 2006), we assume that this sense of self -i.e., entrepreneurial identity -strongly affects their behaviour in how they go about seeking to create and exploit the opportunity.…”
Section: Entrepreneurial Identitymentioning
confidence: 99%
“…In keeping with Mills and Pawson (2011), the everyday life incidents have been shown to encompass amalgam factors, although further research is required to understand how these incidents relate to each other. In particular, acknowledging the importance of timing, identified by De Certeau (1984), there is merit in understanding the temporality of everyday life incidents in the formation of HBBs, but also businesses more generally.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%